PENINGKATAN KEAKTIFAN BELAJAR SISWA MELALUI PERMAINAN GOBAK SODOR PADA MATERI KELINCAHAN - Andina Fara; Mu’arifin, Mu’arifin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to address the low levels of students' learning participation and agility skills caused by limited variation in instructional methods. The objective of this study was to improve students' learning participation and agility through the implementation of the traditional game Gobak Sodor among third-grade students at SDN Sawojajar 5. The research employed a Classroom Action Research (CAR) design consisting of two cycles, each involving planning, implementation, observation, and reflection. The participants were 28 third-grade students. Data were collected through observation, interviews, and the Illinois Agility Test. The results indicated that students' learning participation increased from 37.5% to 89.5%, while the average agility score improved from 68.5 to 85.4, with the mastery level reaching 100%. Therefore, the traditional game Gobak Sodor proved to be an effective learning strategy for enhancing students' learning participation and agility in Physical Education, Sports, and Health (PESH) classes.